3(q-2)+2=5q-72q

Simple and best practice solution for 3(q-2)+2=5q-72q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(q-2)+2=5q-72q equation:


Simplifying
3(q + -2) + 2 = 5q + -72q

Reorder the terms:
3(-2 + q) + 2 = 5q + -72q
(-2 * 3 + q * 3) + 2 = 5q + -72q
(-6 + 3q) + 2 = 5q + -72q

Reorder the terms:
-6 + 2 + 3q = 5q + -72q

Combine like terms: -6 + 2 = -4
-4 + 3q = 5q + -72q

Combine like terms: 5q + -72q = -67q
-4 + 3q = -67q

Solving
-4 + 3q = -67q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '67q' to each side of the equation.
-4 + 3q + 67q = -67q + 67q

Combine like terms: 3q + 67q = 70q
-4 + 70q = -67q + 67q

Combine like terms: -67q + 67q = 0
-4 + 70q = 0

Add '4' to each side of the equation.
-4 + 4 + 70q = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 70q = 0 + 4
70q = 0 + 4

Combine like terms: 0 + 4 = 4
70q = 4

Divide each side by '70'.
q = 0.05714285714

Simplifying
q = 0.05714285714

See similar equations:

| 56x^7+21x^4+9X^3= | | 0=9y^2-64 | | m*7=-18 | | (x-5)*(x-7)=0 | | 10-3(2x+4)=4x+28 | | 2w-8+w^2=0 | | 81x^7+36x^8+63x= | | 0=2x^2-x+2 | | 9x^2+4x+21=0 | | 9=m-0.006 | | 9-6x=45x-4 | | x^2-x+16=0 | | -9x^2+4x+21=0 | | 13x^2-131x-250=0 | | (2+xi)(3-2i)=12+5i | | 2x^2+9x-216=0 | | -x^4+3x^2+x=256 | | -2x+5/2=17 | | x/2+5x/6+x/4=380 | | 0.05x+0.20*300=0.10(x+300) | | 0.05x+0.20*100=0.10(x+100) | | (3x+4)(6x-1)= | | 2w+1(w)-45=0 | | 0.05x+0.20*100mL=0.10(x+100mL) | | (6x+4)(3x-1)= | | 40.77=y/5+2.4y+y/10 | | 12x+15-36-8x=0 | | 2(x^2+7x-141)=0 | | 21-2w-4-w^2=0 | | 2x=4000 | | 26-x=3(x-2) | | 2x*3=12x*4 |

Equations solver categories